Cytotoxic study of Linum usitatissimum and Salvia officinallis extracts on MCF-7 cell line (comparative study) - Shaban, Sama; Ichwan, Solachuddin J. A.; Mustafa Al-Ahmad, Basma Ezzat; Kashmola, Muhanad Ali Hamdon; Mustafa, Nazih Shaban; Taher, Muhammad (2015)

(untitled)
Salvia officinallis and linum usitatissimum are two natural extracts that have been studied before and resulted to have many beneficial values, the research experiment we have done was to investigate weather both of the extracts possess anticancer activities on breast cancer MCF-7 cell line. The MCF.7 cell line was maintained in Dulbecco’s Minimum Essential Medium (DMEM), supplemented with 10% fetal bovine serum (FBS) and 1% of penicillin and grown in 6 cm2 tissue culture dishes. A colorimetric MTT (3-(4,5-dimethythiazol-2-yl)-2,5-diphenyl tetrazolium bromide) assay was used to indicate the cell viability. The MTT test results have shown a slight gradual distraction of breast cancer cells by salvia officinallis oil and water extracts, for linum usitatissimum both oil and water extract have shown little to no growth constriction to MCF-7 breast cancer cells. In this experiment linum usitatissimum showed no cytotoxicity effects on MCF-7 in its both water and oil forms. As for Salvia officinallis there was a little growth constriction effects by its both water and oil extracts on MCF-7 cell line.